Arithmetic Sequential Graceful Labeling on Complete Bipartite Graph - P. Sumathi, G. Geetha Ramani (Mathematical Statistician and Engineering Applications, 2023)
Consider the graph , which has vertices and edges and is simple, finite, connected, undirected, and non-trivial. vertex set is V(G), while its edge set is Let be an injective function from and for each edge defined by . Then the is arithmetic sequential graceful labeling if is bijective. The graph having arithmetic sequential graceful labeling is called arithmetic sequential graceful graph. This paper examined the arithmetic sequential graceful labeling for a few unique graphs.